ANALISIS PRINSIP KESANTUNAN BERBAHASA PADA CERPEN “PAK ADIL MENCARI KEADILAN” KARYA GOL A GONG - Indah Lestari (IKIP Siliwangi, 2020)
The politeness of the language becomes important in communicating. Politeness in communication is a must because it reflects someone being polite and polite in speaking. The politeness of language must be taught from childhood. One application is learning in schools. Short story as one of the subject matter which includes conversations that must also include the principle of politeness in language. The problem that will be discussed in this research is